Risk Mitigation Strategies for The Footwear Industry During The Covid-19 Pandemic - Nugraha, Windy Maudy Atiah Putri; Rahmana, Adhitya; Suroso, Arif Imam (Indonesian Journal of Business and Entrepreneurship, 2022)
CV. XYZ is one of the companies affected by Covid-19, which is marked by a decreased turnover of 70% and as many as 50% of workers are laid off. Risk considerations in business are a concern in the face of an increasingly competitive, unpredictable, and complex business environment. This study aims to identify, analyze and recommend priority operational risk strategies faced by CV. XYZ. The methods used are the Structured What-If Technique (SWIFT) and House of Risk (HOR). The results of this study found thatare that the operational risk events of CV. XYZ are categorized into 3 categories of risk events with a total of 12 risk events. There are 8 of 15 risk-causing agents that contribute 75% to the total ARP, and there are 5 of 17 risk prevention actions that prioritized with the highest Effectiveness Toto Difficulty (ETD) value. Keywords: house of risk, footwear industry, risk management,business processes, business strategy